Raising environmental sustainability care character through Project-Based Learning in English class - Nova, Muhamad (Jurnal Pendidikan Karakter, 2023)
The need for environmental sustainability awareness is rising rapidly and one way to achieve it is through education. This study aimed at unraveling the environmental sustainability care character building through project-based learning in the English for Specific Purpose classroom. This study applied qualitative research with a case study design. This study was conducted at the Politeknik Negeri Bali, and the participants were 39 students from the Tour and Travel Operation study program. The data were collected through observation, documentation, and interview with the students and the lecturer to triangulate the data. The data were then analyzed by data collection, data reduction, data display, and conclusion drawing. This study revealed that the project-based learning method can integrate character-building explicitly by giving a video project on how to take care of rubbish in tourism destinations. Positive responses were also given by the students toward the process of video creation and most of them agreed that they need to take action in taking care of the environment.